Influence of sherardizing on working properties of metal parts subjected to prior heat treatment - V. M. Konstantinov; I. A. Buloichyk (Литьë и металлургия)
The article reveals the data concerning the mechanical properties changes of heat-treated steel articles subjected to thermo diffusion pack cementation. The temperature frames of thermo diffusion influence on tensile strength were determined for heat-treaded steel articles. Results of tensile test of high strength bolts treated using thermo diffusion pack cementation at 420 °C show no any effect from the side of pack cementation treatment on working properties of the tested samples. It is shown that in conditions of cyclic fatigue loading thermo diffusion pack cementation of heat treated article may leads to strength loss that can be explained by formation of solid intermetallic phases in a surface area of the article.